Efektivitas Penggunaan Teknologi Informasi Di Madrasah Ibtidaiyah Negeri 2 Kota Palembang - Fatimah, Nurul; Hestirinaih, Deby Chintia; Zuber, Konar (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
South Sumatra Province has a forest area of ​​3,489,350.37 Ha. While the area of ​​non-forest area is 3,393,469.56 Ha and the area for LP2B is 2,443,324.09 Ha. Every Right Holder, Holder of Management Right, and Holder of Basic Tenure Over Land is obliged to seek, use, utilize, and/or maintain the land that is owned or controlled must have a social function, this is in accordance with the policy formulation of Government Regulation of the Republic of Indonesia Number 20 of 2021 concerning Management of Abandoned Areas and Land which is carried out as land management. The purpose of this study was to analyze the implementation of policies for controlling abandoned areas and lands in the province of South Sumatra. The problem in this research is that there are still lands that are in dispute and there are still many areas that are indicated to be abandoned. The data analysis technique used in this study is a qualitative data analysis technique.This research shows that: overall the Implementation of the Policy for Controlling Abandoned Areas and Land in South Sumatra Province has been carried out properly, although in its implementation there are still obstacles/obstacles such as there are still lands that are in dispute and there are still many areas that are indicated to be abandoned.